The Implementation of the Right to Live in the Families for the Children from the Child Care Home: Approach of the Workers of Child Care Home - Samašonok, Kristina (Pedagogika, 2015)
The importance of family and quality of relations between its members is very important to the process of personal development. The child’s separation from his parents and placement in care homes have long-term consequences to the development of the child. After evaluation of the importance of family for psychosocial development of personality, the attention should be drawn to improve the system of child care for children without parental care. Increasingly it is considered to ensure the child’s right to live the family life, also to return children living in child care homes to their biological parents and to integrate families of foster parents. According to the current situation, the article reveals what trends prevail in practice of home care workers in order to ensure that children live in the families of the biological parents or foster parents. Also the article helps to evaluate the strengths of achievements in performance of employee as well as perceive the existing problems and provide the prospects for improvement of the situation and possible changes. In order for the children not to live at the child care homes, but in families with their parents or guardians, the question arises: what kind of effort has been made by care home staff to ensure the rights of children to live with parents or with a foster family? The aim of the study is to assess the context of the situation from the position of home care workers in order to ensure the right of children to live in the families of parents or foster parents. The peculiarities of the implementation of the right for children from care home to live in the family were analyzed. The study involved 17 care home staff and was based on their view and personal work experience. A semi-standardized interview method has been applied to get to know the strengths of performance achievements of care home staff also to reveal the problems and shortcomings impeding the right of children from care home to live in the family with parents or foster parents and to provide the improvement techniques for the implementation of the child care system. Interviews revealed that the care home staff admits the importance of the relationship between the child and his parents and other family members for the psychosocial development of the child and try to strengthen the relationship between children and their parents .Child care home staff constructs situations for children to meet with parents as often as possible, activate and support communication with the relatives and the loved ones of the ward. The external resources are searched to solve the problems of the wards: children are incorporated into foster families, stimulate foster families to take care of the wards for weekends or holidays, also wards visit the families of home care workers. However, the analysis of activities and experiences of care home staff revealed that not enough attention is paid to solve the problems of wards’ right to live in the family. According to the current situation, care home staff express concerns about the passivity of foster parents and indifference to their children. The care home staff recognizes that usually the one-way communication takes place with families. The employees of child care home dominate by promoting parents to visit their children, while parents remain passive. On the other hand, care home staff believe that solving child custody issues is not enough to provide material support to families of social risk or to record the facts about child neglect, as well as to distinguish it from the destructive social environment and to provide public care. Comments of the research suggest that while solving the questions of welfare of wards and their right to live in the family, it is necessary to improve the work with families that pass on their children’s care to the state custody. It is important to provide parents of wards social-psychological support, to involve them in educational work and solution of relationship problems between ward and his family also it is necessary to include a range of institutions that work with parents. Workers believe that parents need to be given impetus to reform and strengthen their self-confidence and their own capabilities to care of their child and take the responsibility; also it is necessary to encourage parents to get the children back and bring them up the family, to emphasize their importance and necessity to the child. While discussing the opportunities for wards to live in the family, care home staff emphasize the importance of short-term assistance and full care as well as the need to integrate wards into adequate families. It is considered that the integration of the wards into foster families increase the opportunities for children deprived of parental care to build successfully strong families and construct a family relationship. The care home staff agree that living in a care home, foster children form a distorted perception of the family. It is possible to notice the lack of perspective regarding the preparation of foster children and teenagers for their future family life because usually the solutions of problems are restricted to oral remarks or conversations in care homes. Workers of care home believe that the absence of a real family model for wards will impede them to build strong families in the future. Some of the most successful assumptions that could help to reduce rising number of child care institutions are: social assistance and support system in targeting prevention work; provision of services to families by encouraging parents to get the child back to a family; to ensure that social risk families could integrate into the labor market; education and social assistance programs that help to restore a positive family experience, thereby educating the orphans, that grew up in foster homes; education about a family life; the integration and preparation of children psychologically and educationally; taking care of the child’s, families morally and legally.